2021
DOI: 10.1016/j.mayocp.2020.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of COVID-19 With the Mayo Clinic Model of Care and Research

Abstract: Objective: To report the Mayo Clinic experience with coronavirus disease 2019 (COVID-19) related to patient outcomes. Methods: We conducted a retrospective chart review of patients with COVID-19 diagnosed between March 1, 2020, and July 31, 2020, at any of the Mayo Clinic sites. We abstracted pertinent comorbid conditions such as age, sex, body mass index, Charlson Comorbidity Index variables, and treatments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…10 However, lower mortality rates have been observed with the Mayo Clinic model of care and research, as reported in a study that compared Mayo Clinic outcomes in COVID-19 patients with the rates reported nationally. 11 Further, the observed mortality in our study was noted in patients that were older and had comorbidities.…”
Section: Discussionmentioning
confidence: 57%
“…10 However, lower mortality rates have been observed with the Mayo Clinic model of care and research, as reported in a study that compared Mayo Clinic outcomes in COVID-19 patients with the rates reported nationally. 11 Further, the observed mortality in our study was noted in patients that were older and had comorbidities.…”
Section: Discussionmentioning
confidence: 57%
“…The absolute difference in the all-cause hospitalization rate is relatively small but this likely reflects an overall low hospitalization rate at baseline in our clinical practice, and given the continued prevalence of COVID-19, even small absolute differences add up to represent significant public health benefit. 22 This study highlights the potential impact on clinical outcomes that can come from addressing social and cultural factors influencing medical decisions. Interestingly, the difference in hospitalization was magnified in non-White and non-English speaking populations.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rates for patients managed by this model of care were one-third of those observed in national data. 5 Telehealth and Medicine Today ® ISSN 2471-6960 https://doi.org/10.30953/tmt.v6.280…”
Section: Discussionmentioning
confidence: 99%